Surveillance of antimicrobial resistance in the United Arab Emirates: the early implementation phase - Thomsen, Jens; Abdulrazzaq, Najiba M.; AlRand, Hussain; , The UAE AMR Surveillance Consortium; Elhag Ahmed, Ahmed; Yousef, Ahmed F.; AlBlooshi, Amna; latoom, Dr. Adnan; Abdulkareem Al Hammadi, Dr. Ahmed; Enshasy, Dr. Alaa MM; Mubarak Madhi, Dr. Amal; Nabi, Dr. Anju; et al. (Frontiers in Public Health, 2023)
Introduction National surveillance of antimicrobial resistance (AMR) is an important public health function. Published national AMR surveillance data from the Middle East/North Africa (MENA) region is scarce. This paper describes the early implementation phase of establishing AMR surveillance in the United Arab Emirates (UAE). Materials and methods Building on the existing AMR surveillance system in the Emirate of Abu Dhabi, and adopting the WHO-GLASS methodology, the UAE Ministry of Health and Prevention (MOHAP) established the national AMR Surveillance program in 2015, in collaboration with regional health authorities and healthcare providers. Main objectives of this program are to (a) set AMR surveillance standards, (b) collect and analyze AMR surveillance data for common bacterial and fungal infections, (c) report on AMR levels and trends in the UAE, (d) strengthen local and national capacity for AMR surveillance, and (e) support AMR prevention and control strategies in the UAE. AMR surveillance data is collected through a network of 317 surveillance sites (including 84 hospitals and 233 centers/clinics), and 45 microbiology labs across all seven Emirates of the UAE. Results Surveillance of antimicrobial resistance has been successfully established since 2010 in the UAE. A national AMR surveillance protocol has been developed, adopting the WHO GLASS protocol. Extensive capacity-building and training activities have strengthened the local and national capacity for AMR surveillance. Between 2010 and 2021, a network of 317 surveillance sites and 45 laboratories have reported a total of 1,277,080 isolates from 662,065 non-duplicate patients to the national level. AMR data is reported annually by MOHAP through a National AMR surveillance report. National AMR data is utilized for informing the development of standard treatment guidelines at national level. Conclusion National surveillance of antimicrobial resistance has been successfully established in the United Arab Emirates, allowing to monitor levels and trends of antimicrobial resistance for common bacterial and fungal pathogens, and detecting emerging resistance. The availability of such national AMR surveillance data allows for the first time to inform the development of national standard treatment guidelines for empiric treatment of common bacterial and fungal infections in the UAE.